Incorporation of sugarcane bagasse in the development of high dietary fibre noodles - Lau, Ke Qi; Sabran, Mohd Redzwan; Shafie, Siti Raihanah; Chan, Sook Wah (Wiley-Blackwell Publishing, 2022)
Sugarcane bagasse (SB) is one of the most abundant food wastes. In this research, SB was incorporated into the development of noodles at three different ratios, i.e. 5%, 10% and 15%. Total dietary fibre of noodles significantly increased from 3.39% (control noodles; – without SB) to 13.85% with 15% SB incorporation. All SB incorporated noodles (SBNs) were qualified to be labelled as ‘High in dietary fibre’. The 15% SBN had the highest fibre content and lowest dialyzable glucose, but the organoleptic properties were the lowest. Due to that, 5% SBN was deemed to be the most suitable ratio for noodles incorporation, as it had the closest value towards the commercial noodles in terms of colour, texture, fibre content and dialyzable glucose concentration of noodles samples. In terms of sensory evaluation, the 5% SBN had the highest overall acceptability, and the ratio was suitable for noodles development. © 2022 Institute of Food Science and Technology.